Right to education in international law - Rakisheva, A. (Право и государство, 2014)
The article considers the issue of the right to education at the international law. The development of the right to education and the current international instruments which protect the right to education in international law are shown by the author. Generally recognized principles of international law in the field of education determined by international instruments are presented in the paper.
Keywords: international law; right to education; development of right to education; protection; egal instrument; international standard; universal treaty; generally recognized principles; religion; Research Subject Categories::LAW/JURISPRUDENCE